Modern realities of the educational process: competencies of a foreign language teacher - Sharhun Tetiana; Zhukova Anna (Науковий Вісник Південноукраїнського Національного Педагогічного Університету імені К. Д. Ушинського, 2024)
At the present stage, in the context of digital processes development in education, the problem of foreign language teacher competencies is becoming increasingly relevant. Modern teachers need not only to have a thorough knowledge of their specialty, but also to have well-developed intercultural, communication and digital skills. In addition, the need to introduce the latest technologies and teaching methods into the educational process is growing rapidly, which also makes the study of teacher competencies relevant in today's realities. In the article were analysed the key competencies of a foreign language teacher that will enable him/her to work effectively, be successful and highly qualified in his/her field. The paper uses a set of theoretical research methods, including interdisciplinary synthesis and systematic analysis of scientific literature to study in detail the issue of forming foreign language teacher competencies and define the basic concepts of the study; abstraction and concretization, which were used to identify elements of the process of forming modern competencies in teachers of educational institutions; the design method, which was used to substantiate the organizational and pedagogical conditions for the formation of competencies. The main results of the presented study are to define the concept of “modern teacher competence” and to highlight the most important competencies for a foreign language teacher. It has been found that the successful fulfillment of the functional duties of a foreign language teacher involves the formation of a number of competencies, among which the most significant in today's conditions are digital, methodological and communicative competencies. It has been found that at the present stage of development of higher education, a foreign language teacher should constantly acquire new and develop existing competencies, be ready to perform various types of professional activities, continue to improve their knowledge and skills, and participate in professional training in order to remain highly qualified and competent in their field.